A Study on Student’ Speaking Ability of Telling Historical Experience At MA Nurul Wathan Pelangiran - Yogi Arisandi; harum natasha (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
According to 2013 curriculum, the English learning goal is to develop the students’ potential to have the communicative competence in interpersonal, transactional, and functional in written and spoken form. However, according to the preliminary study at Islamic Senior High School Nurul Wathan Pelangiran, the students have difficulties in reaching the passing grades of English; 75. Another thing is teh students have difficultiesnin producing proper vocabularies and good pronunciation. They did not know the appropriate vocabularies while speaking and they often failed to pronounce some words properly. These problems appear to be in educational system where the students have learnt English speaking since the elementary school, but their ability to speak is still low. This research was aimed to find out the students’ speaking abillity of telling historical experience at tenth grade in English Classroom and to know the most dominant component of students’ speaking ability of telling experience at tenth grade of MA Nurul Wathan Pelangiran. This research is a descriptive quantitative research and in collecting the data, the instrument was speaking test. The sample was the total population from social class. The researchers found that the mean score of students’ speaking ability of telling historical experience is 52.50, and categorized as less level. The most dominant component of students’ speaking ability is vocabulary with mean score 2.86 or 57.2%. Students’ speaking is mostly on less level. So the students need to prepare and practice more about speaking. They often pause their speaking during the test, or the students did find it difficult to deal with vocabularies related to historical experience.